What is the degree of segregation between striatonigral and striatopallidal projections? - Jesus eBertran-Gonzalez; Jesus eBertran-Gonzalez; Jesus eBertran-Gonzalez; Denis eHervé; Denis eHervé; Denis eHervé; Jean-Antoine eGirault; Jean-Antoine eGirault; Jean-Antoine eGirault; Emmanuel eValjent; Emmanuel eValjent; Emmanuel eValjent; et al. (Frontiers Media S.A., 2010)
In contrast to most other brain regions, in the striatum the output neurons (the medium-sized spiny neurons, MSNs) are GABAergic and act by inhibiting their targets. The standard model of the basal ganglia is built on the segregation of information processing in the direct and indirect pathways, which act in opposing directions to control movement. The MSNs participating in these two pathways can be identified according to their projection sites and the proteins they express. The differential expression of two of the five known dopamine receptor subtypes, D1 and D2, in the two populations of MSNs is of particular importance, since it confers to dopamine the ability to exert opposite functional modulation on the direct and indirect pathways. However, beyond this simple view of the striatal output organization, anatomical studies questioned the segregation of direct and indirect projections to the SNr, while other studies disclosed variable degrees of overlapping expression of dopamine receptor subtypes in striatal MSNs. New ways to address these issues have emerged recently, using mouse models in which specific populations of striatal neurons are genetically tagged. Here, we review classical and recent studies supporting the segregation of striatonigral and striatopallidal neurons. We also consider this issue at a functional level by focusing on the regulation of striatal signaling pathways in the two populations of MSNs, which clearly emphasize their profound differences. We discuss the anatomical and functional evidence challenging some aspects of this segregation and outline questions that are still to be addressed.